Equity of access and participation in tertiary education in Aotearoa New Zealand: the tale of three regions - Sharon Brownie; Patrick Broman; Cathy Cooney; Leith Comer (Kōtuitui)
‘Access for all’ is a recurring theme in tertiary education. In Aotearoa New Zealand improving access for underserved groups, including Indigenous Māori, is a priority to educational reforms. We undertook a realist evaluation of tertiary education sector participation rates across three regions formerly served by three separate industry training providers. Analysis of enrolment data across the regions reveals ‘educational deserts’ with limited access and low participation in several areas, despite longstanding policy rhetoric regarding equity of access for rural and Māori communities. Patterns are also observed between regions in the level of enrolments outside main population centers, which we argue relate to strategic decisions taken by providers influenced by funding settings. Five considerations arise for policy and leadership practice: (1) the impact of centralisation in creating ‘educational deserts’; (2) the relationship between funding models and an entity’s ability to deliver regionally; (3) the possible impact of international students on domestic students and host organisations; (4) the relationship between ‘belonging’ and tertiary education participation; and (5) an entity’s role in closing equity gaps. Current reforms must move beyond rhetoric and avoid overly centralised education and training provision. Effective policy and resourcing solutions are critical to address current inequities.